2008
DOI: 10.1111/j.1574-6968.2008.01280.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the catalytic activity of the γ-phage lysin, PlyG, specific forBacillus anthracis

Abstract: Bacillus anthracis causes anthrax, a lethal disease affecting humans that has attracted attention due to its bioterrorism potential. PlyG is a lysin of gamma-phage, which specifically infects B. anthracis and lyses its cell wall. PlyG contains a T7 lysozyme-like amidase domain, which appears to be the catalytic domain, in the N-terminal region and has a high degree of sequence similarity with PlyL, which is an N-acetylmuramoyl-l-alanine amidase encoded by the B. anthracis genome. Here, we demonstrated that two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…When analyzed on live bacteria, it was made clear that the B30 endolysin CHAP domain was the primary source of lytic activity from this dual domain endolysin when lysing 'from without' (Donovan et al, 2006b). Site-directed mutagenesis and deletion analysis of the Bacillus anthracis phage lysin PlyG were essential in defining the binding domain and active site residues (Kikkawa et al, 2007;Kikkawa et al, 2008), as for PlyC that was also examined in this way . Similarly, site-directed mutations altering histidine codons in the staphylococcal glycyl-glycine PG hydrolase ALE-1 have been used to define essential amino acids in the M23 endopeptidase domain (Fujiwara et al, 2005).…”
Section: A Swapping And/or Combining Endolysin Domainsmentioning
confidence: 99%
“…When analyzed on live bacteria, it was made clear that the B30 endolysin CHAP domain was the primary source of lytic activity from this dual domain endolysin when lysing 'from without' (Donovan et al, 2006b). Site-directed mutagenesis and deletion analysis of the Bacillus anthracis phage lysin PlyG were essential in defining the binding domain and active site residues (Kikkawa et al, 2007;Kikkawa et al, 2008), as for PlyC that was also examined in this way . Similarly, site-directed mutations altering histidine codons in the staphylococcal glycyl-glycine PG hydrolase ALE-1 have been used to define essential amino acids in the M23 endopeptidase domain (Fujiwara et al, 2005).…”
Section: A Swapping And/or Combining Endolysin Domainsmentioning
confidence: 99%
“…The γ phage is the most well-studied B. anthracis phage due to its diagnostic use and more recently, the proposed use of the lysin enzyme PlyG for decontamination (Fischetti, 2006; Kikkawa et al, 2008; Schuch et al, 2002). γ is morphologically similar to the Siphoviridae family, possessing a long contractile tail and an icosohedral head.…”
Section: Bacteriophagementioning
confidence: 99%
“…Usually, one cell wall binding domain determines the endolysin strain specificity [11,12]; however, there are sometimes more than one [7,13,14] or even no cell wall binding domains [15,16]. The endolysin C-terminus nevertheless sometimes appears to be essential for catalytic activity, as several reports showed that the enzymatic activity is abolished after removal of the C-terminus [17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Because of the multidrug resistance of B. anthracis [21,22], several of its phage or prophage endolysins have been expressed, purified, and characterized. There have also been some attempts to use these endolysins to cure the disease caused by B. anthracis [8,9,11,17,18,23]. Practical applications of endolysins were enabled by studies on functional domain composition, optimal reaction conditions, and species- or strain-specificity.…”
Section: Introductionmentioning
confidence: 99%